Rapid Separation of Human Hemoglobin on a Large Scale From Non-clarified Bacterial Cell Homogenates Using Molecularly Imprinted Composite Cryogels - Hajizadeh, Solmaz; Kettisen, Karin; Bülow, Leif; Ye, Lei (Frontiers in Bioengineering and Biotechnology, 2021)
The production of a macroporous hydrogel column, known as cryogel, has been scaled up (up to 150 mL) in this work for the purification of human hemoglobin from non-clarified bacterial homogenates. Composite cryogels were synthesized in the presence of adult haemoglobin (HbA) to form a molecularly imprinted polymer (MIP) network where the affinity sites for the targeted molecule were placed directly on an acrylamide cryogel by protein imprinting during the cryogelation. The MIP composite cryogel column was first evaluated in a well-defined protein mixture. It showed high selectivity towards HbA in spite of the presence of serum albumin. Also, when examined in complex non-clarified E. coli cell homogenates, the column showed excellent chromatographic behaviour. The binding capacity of a 50 mL column was thus found to be 0.88 mg/g and 1.2 mg/g, from a protein mixture and non-clarified cell homogenate suspension, respectively. The recovery and purification of the 50 mL column for separation of HbA from cell suspension were evaluated to be 79% and 58%, respectively. The MIP affinity cryogel also displayed binding and selectivity towards fetal Hb (HbF) under the same operational conditions.